2015
DOI: 10.1021/acs.est.5b02617
|View full text |Cite|
|
Sign up to set email alerts
|

Levels of Phthalate Metabolites in Urine of Pregnant Women and Risk of Clinical Pregnancy Loss

Abstract: Toxicological studies have shown that phthalate esters (PAEs), a class of widely used and environmentally prevalent chemicals, can increase the abortion rate in animals, but epidemiological evidence is scarce. This study aimed to explore the relationship between the urinary concentration of phthalate metabolites and the risk of clinical pregnancy loss. A total of 132 women who underwent clinical pregnancy loss (cases) and 172 healthy pregnant women (controls) were recruited from Beijing, China. Eight phthalate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 49 publications
(81 reference statements)
4
42
0
Order By: Relevance
“…7,13,30 Our results are consistent with those of a Danish study by Toft and colleagues, who examined pregnancy loss, defined as subclinical embryonal losses and clinical losses combined. 7 The authors enrolled couples planning their first pregnancy after discontinuation of birth control, and followed them prospectively until a clinically recognized pregnancy occurred or for six menstrual cycles.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…7,13,30 Our results are consistent with those of a Danish study by Toft and colleagues, who examined pregnancy loss, defined as subclinical embryonal losses and clinical losses combined. 7 The authors enrolled couples planning their first pregnancy after discontinuation of birth control, and followed them prospectively until a clinically recognized pregnancy occurred or for six menstrual cycles.…”
Section: Discussionsupporting
confidence: 91%
“…Three recent studies have examined the effect of various phthalates on pregnancy loss in couples conceiving naturally with conflicting results. 7,13,30 Others have investigated the effect of phthalates on gestational length 3133 and preterm birth 34,35 with varying methods and conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all of the non-cancer and carcinogenic risks to humans for PAEs were due to direct intake of the edible parts8. PAE intake may pose a special health hazard to vulnerable populations such as pregnant women and children454. Even when the overall health risk of PAE is low in maize and wheat crop systems, the potential damage of PAE to human health via long-term exposure to low doses may still deserve further attention.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, epidemiological studies revealed that in utero exposure to some phthalates was associated with pregnancy complications (e.g. spontaneous abortion and increased blood pressure) (Jukic et al, 2016;Mu et al, 2015;Toft et al, 2012;Werner et al, 2015), adverse birth outcomes (e.g. preterm birth, low birth weight and decreased birth length) Huang et al, 2009;Latini et al, 2003;Meeker et al, 2009;Minatoya et al, 2017;Philippat et al, 2012;Wolff et al, 2008;Zhang et al, 2009), and impaired children growth (Valvi et al, 2015) and neurodevelopment (e.g.…”
Section: Introductionmentioning
confidence: 99%